De HIV-test, niet zomaar een test - Avonts, Dirk; Groen, G. van der; Piot, Peter (Antwerpen: Instituut voor Tropische Geneeskunde (ITG))
"D. Avonts, G. van der Groen, P. Piot Fonds Suzan Daniel (FSD)"